Outcome of antibiotic treatment in patients with abdominal trauma at the hospital in Ceilândia - Rosales, Rolando Gutierrez; Filho, Jandui Gomes de Abreu; Santana, Karoliny Araujo; da Silva, Nailton Gomes; Rocha, Déborah de Fatima Diniz; de Paula, Mozart Borges; Andrade, Bruno Bessa; Rosa, Kenya Correa; Sanches, Matheus Savindo Batista (Seven Editora, 2024)
Infections generate complications capable of causing morbidity and mortality in trauma patients. As a measure to prevent infections, the administration of antibiotics should be early. However, the use of antibiotics for a long time is not recommended, since there is no evidence of a favorable outcome, in addition to increasing health care costs. Due to the need to prevent infections in trauma patients, it is important to adopt strict control measures with the implementation of effective strategies to improve health care for these patients. The aim of this study was to evaluate the impact of antibiotic use in trauma patients in a hospital in Brasilia. This research is an observational cross-sectional investigation, based on a retrospective approach through the extraction of data from the health information system "TrackCare". The participants of this research comprise patients with abdominal trauma who underwent surgical treatment from January to December 2021. It is observed that almost half of the 93 patients were assigned to receive antibiotic therapy or antibiotic prophylaxis. Within this selected group, the main antimicrobial agent chosen was Unasyn, a combined composition of Ampicillin with Sulbactam, covering approximately 31% of cases. In this context, it is urgent to consider that the selection of the antimicrobial agent is not only based on its efficacy, but also on its adequacy to the particularities of the clinical picture presented by the patient. DOI:https://doi.org/10.56238/sevened2024.016-005